An Overview of the Impact of Green Finance on Green Total Factor Productivity - Meng-yao Zhan; Mu Zhang (Journal of Risk Analysis and Crisis Response (JRACR))
This paper discusses the impact of green finance on the green total factor productivity of enterprises, and aims to summarize and analyze the research dynamics, trends and key issues of green finance on green total factor productivity. Since China put forward the goal of “double carbon”, green finance has become an important tool for optimizing resource allocation, enhancing technological innovation and measuring high-quality development in new industries, and its impact has been widely reflected in the social, scientific, technological and economic fields. The purpose of this paper is to comprehensively analyze the research results on the impact of various aspects of green finance on green total factor productivity, including green finance as a whole, green bonds, carbon finance and green credit, and provide theoretical references and practical guidance for future policymaking. Finally, this review discusses the outlook of the relationship between green finance and green total factor productivity in the future.